1996
DOI: 10.1111/j.1699-0463.1996.tb00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid in type 2 (non-insulin-dependent) diabetes

Abstract: Amyloid deposits are found in pancreatic islets of 90% of type 2 (non-insulin-dependent) diabetic subjects at postmortem. Islet amyloid is formed from islet amyloid polypeptide (IAPP). IAPP is a 37 amino acid peptide which is a normal constituent of p cells and is co-secreted with insulin in animals and in man. The causative factors for fibrillogenesis of IAPP are unclear, but could be related to the sequence of IAPP and abnormal production of the peptide. The lack of islet amyloid in rodent models of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
(21 reference statements)
0
26
0
Order By: Relevance
“…Because of differences in sample size and diagnostic criteria, the prevalence of islet amyloid reported in type 2 diabetic patients varies substantially (4,5,10). For example, the widely cited study by Westermark and Wilander (31) showed that islet amyloid was found in 100% of their sample of only 12 Caucasian patients with adult onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of differences in sample size and diagnostic criteria, the prevalence of islet amyloid reported in type 2 diabetic patients varies substantially (4,5,10). For example, the widely cited study by Westermark and Wilander (31) showed that islet amyloid was found in 100% of their sample of only 12 Caucasian patients with adult onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…IAPP is the building block of islet amyloid deposits (5,10,24). Although Congo red is not a specific marker for IAPP, it is as sensitive a marker for islet amyloid as IAPP immunolabeling (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found an association of this ␤-cell failure with the deposition of islet amyloid in the pancreas (3). We and others have previously reported the generation of transgenic animal models that exhibit human islet amyloid polypeptide (huIAPP)-dependent hyperglycemia associated with loss of ␤-cell mass and/or amyloid deposition (3)(4)(5). One model is described herein as the Lean-huIAPP transgenic line [FVB/N-Tg(IAPP)6Jdm/Tg(IAPP)6Jdm] (6).…”
mentioning
confidence: 94%
“…Diabetes 51:2158 -2169, 2002 T ype 2 diabetes is characterized by both impaired insulin action (1) and failure of ␤-cells to compensate with increased insulin secretion (2). Some studies have found an association of this ␤-cell failure with the deposition of islet amyloid in the pancreas (3). We and others have previously reported the generation of transgenic animal models that exhibit human islet amyloid polypeptide (huIAPP)-dependent hyperglycemia associated with loss of ␤-cell mass and/or amyloid deposition (3)(4)(5).…”
mentioning
confidence: 99%